The Effect of The Use of Snake Media on Students Learning Interests - Mulyawati, Yuli; Windiyani, Tustiyana (International Conference on Elementary Education, 2021)
The purpose of this study to determine the effect of media usage snake and ladder on student interest in Primary School. This study used a Kausal design. This research was conducted in Class 4 SDN Katulampa 1 Bogor City in the odd semester of the 2020/2021 school year. The analysis technique used is the analysis prerequisite test which includes the normality test, homogeneity test, then the research hypothesis is carried out using the t-test. Based on the results of research in grade 4 SDN Katulampa 1, there is a significant influence between media use snake and ladder with student interest in learning, this can be shown from the results of the correlation coefficient (rxy) of 0.78 which shows that there is a strong influence of the variable use of snake and ladder media on student interest in learning and the tcount is 8,480. This is also evidenced by the regression equation Å¶ = -58,23 + 1.5 X, meaning that each increase in the use of snake and ladder media will increase student interest in learning by 1.5 units. Besides, the results of the coefficient of determination r 2 = 0.60, which means that the snake and ladder learning media contributed 60% to the interest in learning, while other factors contributed 40%. This shows that there is an effect of using the snake and ladder media on students' interest in learning